1983
DOI: 10.2337/diacare.6.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Foot Pressure and Other Studies as Diagnostic and Management Aids in Diabetic Neuropathy

Abstract: The pressures and loads under the feet during walking have been compared in three groups of 41 patients each, using a microprocessor-controlled optical system. Group A consisted of patients with diabetic neuropathy, group B of non-neuropathic diabetic patients, and group C of nondiabetic controls. Thirteen patients in group A had a history of neuropathic foot ulceration. Other investigations in the diabetic patients included motor conduction velocity (MCV) in the median and peroneal nerves, vibration perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
178
2
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(185 citation statements)
references
References 10 publications
3
178
2
2
Order By: Relevance
“…After our initial confirmation that plantar ulcers invariably occurred at sites of high pressure [35], we demonstrated that foot pressure abnormalities occur early in the natural history of neuropathy [51]. In a longitudinal study it was confirmed that sites of peak pressure change over time, an observation with important implications for orthotists [52].…”
Section: Foot Pressure Studies In Diabetesmentioning
confidence: 73%
See 1 more Smart Citation
“…After our initial confirmation that plantar ulcers invariably occurred at sites of high pressure [35], we demonstrated that foot pressure abnormalities occur early in the natural history of neuropathy [51]. In a longitudinal study it was confirmed that sites of peak pressure change over time, an observation with important implications for orthotists [52].…”
Section: Foot Pressure Studies In Diabetesmentioning
confidence: 73%
“…The association between both somatic and autonomic neuropathy and foot ulceration has been recognised for many years [35]. It is only in the last decade that prospective follow-up studies have confirmed this causative role of somatic neuropathy [12,18,19].…”
Section: Causal Pathways To Foot Ulcerationmentioning
confidence: 99%
“…The most increased pressure measurement in one defined region represented the maximal peak pressure. According to previous studies, maximal peak pressure directly correlates with the risk for developing mechanicalinduced forefoot complaints [2,16]. Maximal force was the most increased force in one defined anatomic region (F = p/A).…”
Section: Methodsmentioning
confidence: 79%
“…There is also considerable evidence that abnormal plantar pressures occur in the diabetic foot (Boulton et al 1983, Stess et al 1997. Plantar ulcers do not normally occur in the absence of pressure and a reduction in pressure is the normal pre-requisite for healing (Cavanagh and Ulbrecht 1994).…”
Section: Rationalementioning
confidence: 99%
“…By considering the findings from several clinical studies, Cavanagh and Ulbrecht (1992) have suggested several factors that may affect the pressure thresholds for plantar tissue breakdown: variation between different plantar sites; adequacy of the vascular supply, and tissue perfusion; glycosylation of the tissues; the presence of scar tissue; the duration for which pressure is applied rather than peak pressure. Boulton et al (1983) first concluded plantar pressure in the diabetic could increase with time. This is supported by the findings of Veves et al (1992) who measured plantar pressure in three subject types over a thirty-month period.…”
Section: Optical Properties Of the Skin And Bloodmentioning
confidence: 99%